Answer:
(x-3)(x+6)
Step-by-step explanation:
Given the polynomial: x²+3x-18
To factor it, first, we multiply the first and last terms.
![-18* x^2=-18x^2](https://img.qammunity.org/2023/formulas/mathematics/college/y4rpcsrxj644z3j49egw3uk6vh622lwh07.png)
Next, we list add factors of -18.
![\begin{gathered} -18=-1*18 \\ -18=-2*9 \\ -18=-3*6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lyh4pcpaxvn8su36o1qpw0gykhdnepiy8c.png)
Next, we determine the factors that add up to the middle term: 3x
These factors are: 6x and -3x.
Replacing the middle term, we have:
![\begin{gathered} x^2+6x-3x-18 \\ =x(x+6)-3(x+6) \\ =(x-3)(x+6) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5ts35c6u9scdv6o0suv0vtup2rgvbjjmoe.png)